TINGKAT PENGETAHUAN IBU NIFAS TENTANG PERAWATAN TALI PUSAT BAYI BARU LAHR DI RSUD WONOSARI GUNUNGKIDUL YOGYAKARTA - Nurul Ariningtyas (STIKES Wira Husada Yogyakarta, 2019)
Background: The 2015 Census Population Survey (SUPAS) result shows that infant mortality rate (IMR) in Indonesia is 22.23 per 1,000 live births, which means reaching 2015 MDG target is 23 per 1,000 live births1. Infant mortality born at 79% occurs every first week of birth especially at the time of delivery. A total of 54% occurred at the family level due largely to inadequate referral services and lack of family knowledge of emergency emergencies in infantsObjectives: To know the level of knowledge of postpartum mother about cord newborn care in Wonosari Hospital, Gunung Kidul.Method: This research was conducted by analytical descriptive method. Descriptive analytic research is a study that describes the object diteiti through sample data or population how it is, without doing analysis and make conclusions that apply to the public.Result: Based on the result of research of maternal post-natal knowledge about cord nursing care in RSUD Wonosari Gunung Kidul there are maternal respondent respondents good knowledge 7 respondents (23,4%), enough 10 respondents (33,2% ), less 13 respondents (43,4%).Conclusion: Based on the research result, the knowledge level of postpartum mother about the treatment of talipusat newborn in RSUD Wonosari Gunung Kidul Yogyakarta still less.